Computed-Tomography-Structured Reporting in Middle Ear Opacification: Surgical Results and Clinical Considerations From a Large Retrospective Analysis - Cavaliere, Michele; Di Lullo, Antonella Miriam; Russo, Camilla; Mesolella, Massimo; Cantone, Elena; Di Lorenzo, Giuseppe; Motta, Gaetano; Elefante, Andrea (Frontiers in Neurology, 2021)
Purpose: Aim of the study is to compare the accuracy of unstructured preoperative Computed Tomography (CT) reports from non-tertiary diagnostic centres with intraoperative findings in a large cohort of patients with Chronic Otitis Media (COM) undergone surgery. Methods: From 2012 to 2019, a total number of 301 patients were considered for our purposes. All patients with clinical evidence of COM had preoperative non-contrast high resolution CT scan of the temporal bone in non-tertiary diagnostic centres, performed within 3 months before surgery. Results: The accuracy of CT reports was analysed in terms of nature, anatomical site, disease extension, bony erosion, vascular structures abnormalities relevant to surgical planning, and Eustachian tube patency. Compared to post-surgical findings, CT reporting critical analysis revealed a tendency to overestimation of bony erosion, coupled to underestimated description of facial canal/lateral semicircular canal, vascular structures and Eustachian tube. Conclusion: Discrepancies between CT reports and surgical findings in middle ear opacification can be at least in part due to limited expertise of general radiologists in ENT neuroimaging. To limit this lack of information and the limited accuracy of middle ear structures depiction, here we propose a structured checklist to adopt in case of temporal bone CT scan for COM, in order to optimize the communication with surgeons and provide all the crucial information for an accurate surgical planning.